2020
DOI: 10.1371/journal.pone.0240399
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of believing you have had COVID-19 on self-reported behaviour: Cross-sectional survey

Abstract: Objectives To investigate whether people who think they have had COVID-19 are less likely to report engaging with lockdown measures compared with those who think they have not had COVID-19. Design On-line cross-sectional survey. Setting Data were collected between 20 th and 22 nd April 2020. Participants 6149 participants living in the UK aged 18 years or over. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 15 publications
7
48
4
Order By: Relevance
“…These low rates of symptom recognition are comparable to those found in other UK research 91429. Recognising that symptoms might be indicative of covid-19 is a first step in the chain that leads to isolation when required.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…These low rates of symptom recognition are comparable to those found in other UK research 91429. Recognising that symptoms might be indicative of covid-19 is a first step in the chain that leads to isolation when required.…”
Section: Discussionsupporting
confidence: 88%
“…Reduced adherence to social distancing measures has also been reported in this group. 14 Other research has found an association between higher education and poorer adherence to UK government guidance. 45 Working in a key sector was also associated with not fully self-isolating.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations